Efeitos das mudanças climáticas e da extinção da megafauna na vegetação do Brasil - Oliveira, Jacqueline Freitas (2021)
The end of the South American Pleistocene was characterized by great climatic variations that impacted all living organisms and led to the extinction of a large part of the megafauna. From this, several discussions arose about the causes and consequences of this extinction. In this study we investigate the relationship between climate change from the last glacial cycle, megafauna extinction and changes in terrestrial vegetation in Brazil. To find this relationship, we made a temporal correlation between dated megafauna fossils with pollen diagrams in four Brazilian regions: Central, Northeastern, Northwestern, and Southeastern. Of the four regions studied, only the Northeastern region had pollen data and adequate dates to carry out the complete analysis. Despite the lack of records dated in the Central, Northwestern and Southeastern regions, it was possible to analyze its vegetation over time. In all regions, it was possible to conclude that climate change was responsible for the extinction of the megafauna, but in the Northeast region the vegetation was still stable when it became extinct locally. In the Northeast, Northwest and Southeast regions, it was possible to identify that the absence of megafauna added to climatic effects altered the vegetation, while for the Central region it was possible to conclude that its absence did not influence the vegetation. Thus, the effects of the extinction of megaherbivores on vegetation depend on the ecosystem from which they were excluded.